2006
DOI: 10.1097/01.rli.0000236825.72344.a9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microbubble Ligation to Cells on Ultrasound Signal Enhancement

Abstract: Attachment of targeted microbubbles to rigid surfaces results in damping and a reduction of their acoustic signal, which is not seen when microbubbles are attached to cells. A reliable concentration versus intensity relationship can be expected from microbubble attachment to 2-dimensional surfaces until a very high site density is reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…In these mice, both CEU and en face microscopy were consistent with a diffuse and widespread attachment of VCAM-1-targeted microbubbles, the density of which was within the dynamic range for detection of microbubbles attached to a 2-dimensional surface. 27 The diffuse nature of attachment suggests that a surrogate large vessel may be used for evaluation when vascular inflammatory status is severe, although this was not directly tested. In ApoE Ϫ/Ϫ mice on chow diet, attachment of microbubbles targeted to VCAM-1 was more pronounced in regions of atherosclerotic plaque, consistent with reports on upregulation of VCAM-1 predominantly in regions prone to plaque development.…”
Section: Evaluation Of Disease Severitymentioning
confidence: 99%
“…In these mice, both CEU and en face microscopy were consistent with a diffuse and widespread attachment of VCAM-1-targeted microbubbles, the density of which was within the dynamic range for detection of microbubbles attached to a 2-dimensional surface. 27 The diffuse nature of attachment suggests that a surrogate large vessel may be used for evaluation when vascular inflammatory status is severe, although this was not directly tested. In ApoE Ϫ/Ϫ mice on chow diet, attachment of microbubbles targeted to VCAM-1 was more pronounced in regions of atherosclerotic plaque, consistent with reports on upregulation of VCAM-1 predominantly in regions prone to plaque development.…”
Section: Evaluation Of Disease Severitymentioning
confidence: 99%
“…The first question, as was stated by Lindner [8], is whether bubbles adhering to a target cell produce strong enough acoustic signals. It was found that the response of adherent microbubbles is comparable to that of phospholipid-coated microbubbles [96,97]. However, it remains to be seen if the concentration of adherent microbubbles in vivo will be high enough to produce signals in the order of normal contrast-enhanced ultrasound in perfusion imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it would be beneficial to distinguish acoustically between adherent and freely circulating microbubbles. Considerable changes between adherent and non-adherent microbubbles were found, such as a decrease in the acoustic response of adherent microbubbles with respect to non-adherent microbubbles [96] and a change in the spectral response [97]. In chapters 6 and 7 of this thesis it was shown that the close proximity of a wall changes the bubble dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However they oscillate less efficiently and generate a smaller amplitude signal compared to freely circulating microbubbles (27,39). On the other hand, it has been shown that attachment of targeted microbubbles to a cell surface such as endothelial cells, will improve stability of microubbles over time without damping the signal (40,41).…”
Section: Detection Of Targeted Microbubbles: Imaging Strategiesmentioning
confidence: 99%